Same-sex sexual behavior of men in Kenya: Implications for HIV prevention, programs, and policy - Geibel, S. (Universa Press, 2012)
Unprotected anal sex has long been recognized as a risk factor for HIV transmission among men who have sex with men (MSM). In Africa, however, general denial of MSM existence and associated stigma discouraged research. To address this gap in the literature, partners conducted the first behavioral surveys of MSM in Kenya. The first study was to assess HIV risk among MSM in Nairobi, and the second study a pre-post intervention study of male sex workers in Mombasa. The 2004 behavioral survey of 500 men in Mombasa revealed that MSM were having multiple sexual partners and failed to access appropriate prevention counseling and care at Kenya clinics. A 2006 capture-recapture enumeration in Mombasa estimated that over 700 male sex workers were active, after which a pre-intervention baseline survey of 425 male sex workers was conducted. Awareness of unprotected anal sex as an HIV risk behavior and consistent condom use with clients was low, and use of oil-based lubricants high. Based on this information, peer educators were trained in HIV prevention, basic counseling skills, and distribution of condoms and lubricants. To assess impact of the interventions, a follow-up survey of 442 male sex workers was implemented in 2008. Exposure to peer educators was significantly associated with increased consistent condom use, improved HIV knowledge, and increased use of water-based lubricants. These results have provided needed information to the Government of Kenya and have informed HIV prevention interventions.